THE USE OF INDIRECT FEEDBACK TO REDUCE STUDENTS’ GRAMMATICAL ERRORS IN WRITING AN ANALYTICAL EXPOSITION TEXT - Annisa Bintang Kusumawardhani (Journal of English and Education, 2015)
Feedback provision is a necessity for students in the process of writing. Thus, this research aims to discover the use of indirect feedback to reduce students’ grammatical errors in writing an analytical exposition text. Furthermore, this study was conducted to find out students’ response toward indirect feedback given as treatment. The study implemented a quasi- experimental design. The sample of this study involves 60 students as control group and experimental group. Students’ writing and questionnaire were used to obtain the data in this study. Afterwards, one way analysis of variance test in SPSS 20.0 conducted to analyze the data. Based on the statistical result, after indirect feedback was implemented on students’ writing, the level of significance is .000 or 0.05, thereby the null hypothesis was rejected. Thus, the use of indirect feedback reduces the number of grammatical errors made by students in writing an analytical exposition text. In addition, from the questionnaires’ result, students’ gave positive responses toward indirect feedback.